Pemetaan Pengembangan Karir Jabatan Analis Pengembangan SDM Aparatur Pada BKPP Kota Bandung - Pradia Fajar Ramadhana; Edah Jubaedah; Sutarto Mochtar (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2022)
Human resources have an important role in the progress of an organization, including in government agencies. To be able to answer the public in conducting public services, the development of employees of the State Civil Apparatus (ASN) to realize the State Civil Servants who have integrity and professionalism in the work process becomes an obligation for every government agency. That way, the competitive advantage of an organization is highly determined by its Human Resources. Handling of human resources must be carried out thoroughly within the framework of a strategic, integrated, interrelated, and unity human resource management system. Government agencies really need competent human resources, have certain competencies needed to support the successful implementation of their work. The purpose of this research is to look at mapping position of personnel human resource development analyst in the Bandung City Education and Training Personnel Agency. The method used in this research is descriptive. The results of this study is the obtaining of recommendations on mapping the career development of the position of human resources development analyst in the Education and Training Staffing Agency bandung city deserves to be directed to get a promotion.